Analysis of Financial Reports at BUMDES Tambaksari Village, Rubaru District, Sumenep Regency Based on SAK ETAP - Zainuddin, Mohammad; Suprihandari, Miya Dewi; Raharjo, Kusuma Adi; Subandoro, Agus (CV. Proaksara Global Transeduka, 2024)
This study aims to assess the compliance of the financial statements of Village-Owned Enterprises (BUMDes) in Tambaksari Village with the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). It adopts a qualitative research approach, conducting thorough observations and analysis of BUMDes financial statements. Data collection methods include descriptive qualitative techniques, interviews, documentation, and literature studies pertaining to SAK ETAP-based financial reporting. The findings reveal several challenges, notably the non-compliance of financial statements with SAK ETAP and a lack of awareness among BUMDes in Tambaksari Village regarding financial report analysis, attributed to limited knowledge.